The possible usefulness of a medium cut-off dialyzer in a patient with cardiomyopathy of unclear origin - Szewczyk, Bartłomiej; Hołownia, Kamila; Jaroszyński, Andrzej (Medical Studies/Studia Medyczne, 2022)
The large middle molecules are a specific class of uremic toxins, which includes compounds like interleukins 1, 6, 18, tumor necrosis TNF-b, and free light chains (FLCs). Accumulation of these molecules is associated with cardiovascular complications in end-stage renal disease (ESRD). Medium cut-off (MCO) membrane provides the ability to remove large middle molecules effectively with marginal albumin leak. We present the case of 59-year-old male patient with ESRD. He was admitted to the Nephrology Clinic because of deteriorating heart failure. Moreover, the patient suffered from unclear origin cardiomyopathy. He underwent percutaneous coronary intervention. Due to worsening outcome, an attempt to use MCO treatment was made. After 6 months of MCO treatment, the patient’s clinical condition improved spectacularly. This is the first case report of the use of MCO treatment in a patient with a cardiomyopathy of unclear origin. Our study suggests that using MCO treatment in such cases may be advisable.